Phosphorylation of murine mammary tumor virus precursor polypeptides. - Racevskis, J (1979)
Phosphorylation of the murine mammary tumor virus (MuMTV) structural proteins was studied in an MuMTV-infected epithelial cell line derived from a BALB/cf C3H mouse mammary tumor. Immunoprecipitation of 32P-labeled cell extracts with monospecific anti-p27 serum revealed that phosphorylation occurred at the stage of the core-protein polyprotein precursor prp75. Two forms of phosphorylated prp75 were found: one migrating with an apparent molecular weight of 80,000, and the other with a molecular weight of 76,000. The 80,000-molecular-weight species was found to be the most heavily phosphorylated. In addition, a relatively stable phosphorylated processing intermediate of 34,000 molecular weight was observed as well. Tryptic peptide mapping analysis of the 32P-labeled viral proteins indicated a precursor product relationship between the intracellular phosphorylated, high-molecular-weight peptides and the mature MuMTV phosphoproteins p23 and p27. Phosphopeptide analysis also suggested that phosphorylation of the viral proteins occurred in discrete steps and that the attached phosphate groups were conserved throughout the processing steps.